A priority-considering approach for the multiple container loading problem. (1st January 2011) - Ren, Jidong; Tian, Yajie; Sawaragi, Tetsuo
A priority-considering heuristic approach is proposed to solve the multiple container loading problem, i.e., the problem of packing a given set of three-dimensional rectangular items into multiple containers to make the maximum use of the container space. The items with large volume are usually difficult to make efficient use of the container space. These items are set higher priority over other items, and preferentially assigned into the containers. Within the proposed approach an algorithm is used for solving the single container loading problem under the constraint of priority. The proposed approach achieves excellent results for the test cases suggested by Ivancic et al. and Mohanty et al. with reasonable computing time.